2022
DOI: 10.1186/s12905-022-01925-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with an unfavorable clinical course in hospitalized patients with pelvic inflammatory disease: a retrospective cohort study of 117 patients from a Japanese academic institution

Abstract: Background This study aimed to determine the factors associated with an unfavorable clinical course (emergency surgery and/or prolonged hospitalization) in patients requiring hospitalization owing to pelvic inflammatory disease (PID). Methods A retrospective study was performed on 117 patients diagnosed with PID who were admitted to our hospital between January 2014 and December 2018. Multivariate regression analysis was conducted to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Firstly, the infiltration of macrophages and abnormal activation of vascularization in endometriosis lead to adhesions and structural changes in pelvic organs. [20][21][22] Subsequently, these altered structures make it easier for bacteria to thrive, thus increasing the risk of PID. Secondly, the presence of stagnant blood in endometriotic lesions may raise the pH of surrounding organs, impacting the local microbial environment, lead to bacterial infection, and subsequently induce PID.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the infiltration of macrophages and abnormal activation of vascularization in endometriosis lead to adhesions and structural changes in pelvic organs. [20][21][22] Subsequently, these altered structures make it easier for bacteria to thrive, thus increasing the risk of PID. Secondly, the presence of stagnant blood in endometriotic lesions may raise the pH of surrounding organs, impacting the local microbial environment, lead to bacterial infection, and subsequently induce PID.…”
Section: Discussionmentioning
confidence: 99%
“…[21] A retrospective study from Japan found that obesity prolongs hospitalization for PID. [6] Obesity has been shown to impair immunological response by generating pro-inflammatory substances in adipose tissue and affecting T-cell activity. [22] Similarly, investigations have linked overweight status, as well as obesity classes I, II, and III, to heightened risks of endometritis subsequent to vaginal, non-instrumental deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] In addition, recurrent episodes of PID can burden society and the healthcare system. [6] Thus, investigating the risk factors linked to PID is crucial for offering early interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Before reaching a copper intake of 0.85 mg/day (close to the RDA), the link between copper intake and PID in the overweight subgroup (≥30.0 kg/m 2 ) was flat and decreased rapidly when the RDA of copper was reached. A retrospective study has shown that obese PID patients were identified to be associated with an unfavorable clinical course ( 9 ). Thus, adequate copper intake may become even more important for older and overweight women with PID.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, approximately 0.5 to 1 million cases of PID develop annually, and the average cost is up to $3,025 per episode for PID therapy ( 7 , 8 ). At the same time, the majority of PID patients are prone to experience disease recurrence, resulting in additional burdens on society and healthcare systems ( 9 ). Hence, it is crucial to examine the risk factors associated with PID to enable early intervention.…”
Section: Introductionmentioning
confidence: 99%